Motivation features of tennis players aged 10-12 - Ivanova, T.S. (Theory and Practice of Physical Culture, 2026)
Objective of the study is to optimise the educational and training process of young tennis players aged 10-12 based on the study of the features of their motivation. Methods and structure of the study. Analysis of scientific and methodological literature, questionnaires and surveys of athletes, coaches, as well as parents of children involved in tennis, pedagogical experiment, methods of mathematical statistics. The study was conducted in 2023-2026 at tennis centres and sports schools in Moscow. 58 people took part in the survey and questionnaire, including 24 parents and 8 coaches, and the experimental work involved a group of 14 tennis players. Results and conclusions. The dynamics of motivation features of young tennis players aged 10-12 and their parents were analysed in comparison with analogous data of tennis players under 10 years of age and aged 12-14 and older. The research results make it possible to use the obtained information not only directly in sports training, but also in everyday life, during the daily pedagogical process of educating the younger generation. Moreover, the systematisation of the obtained results makes it possible to make the preparation process continuous, smoothly transitioning to the next stage of development, using general principles to ensure better understanding and interaction with the player at each stage of this development.